Zagraniczne istnienie literatury polskiej - Pasterska, Jolanta; Luboń, Arkadiusz; Wyrembelski, Marcin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Interest in reception of Polish literature translated into foreign languages has increased in recent years among not only academic researchers but also publishers, literary critics and readers as well. Both successes of contemporary Polish writers abroad and the endeavors of cultural institutions aimed at promotion of Polish literature in other countries inspire discussions centered on the issue of selection and adaptation of the most representative, unique and/or attractive for foreign readers texts, originally written in Polish. The tenth issue of „Tematy i Konteksty” also addresses these questions, collecting papers focused, among others, on modern translator’s cultural role and status, standard or unconventional techniques and methods applied in literary translation, particular transfers of various artistic texts from Polish into other languages and modes of their reception within target cultures. Articles collected in the volume answer numerous questions related, for instance, to the ways in which foreign readers respond to writings by Polish authors or to the fields of discourse texts of Polish origin enter as an effect of the set of translational transformations. These transformations result from a variety of factors, such as translator’s idea of equivalence, his/her professional and social position, editorial strategies or even detailed choices of lexical items crucial for the preconceived meaning of the text. The articles discussing and analyzing such issues unveil the secret of supralocal successes of certain Polish writers and clearly indicate the importance of translator’s work for their achievements.
Foreign Existence of Polish Literature
Keywords: Polish literature abroad; critical reception; literary translation; culture promotion; translator’s status; literatura polska poza krajem; recepcja krytyczna; przekład literacki; promocja kultury; status tłumacza